Immunohistological analysis of pancreatic carcinoma after vaccination with survivin 2B peptide: Analysis of an autopsy series. Issue 8 (11th July 2019) - Kubo, Terufumi; Tsurita, Giichiro; Hirohashi, Yoshihiko; Yasui, Hiroshi; Ota, Yasunori; Watanabe, Kazue; Murai, Aiko; Matsuo, Kazuhiko; Asanuma, Hiroko; Shima, Hiroaki; Wada, Satoshi; Nakatsugawa, Munehide; et al.
Abstract: Immune checkpoint inhibitors (ICIs) have revolutionized the treatment of cancer by providing new options in addition to existing therapies. However, peptide vaccination therapies still represent an attractive approach, because of the antigen specificity. We identified survivin 2B peptide (SVN‐2B), a 9‐mer antigenic peptide encoded by survivin, and an SVN‐2B peptide vaccine‐based phase II randomized clinical trial targeting unresectable and refractory pancreatic carcinoma was undertaken. The SVN‐2B peptide vaccine did not have any statistically significant clinical benefits in that study. Therefore, we undertook an autopsy study to analyze the immune status of the pancreatic cancer lesions at the histological level. Autopsies were carried out in 13 patients who had died of pancreatic cancer, including 7 who had received SVN‐2B peptide vaccination and 6 who had not, as negative controls. The expression of immune‐related molecules was analyzed by immunohistochemical staining. Cytotoxic T lymphocytes were analyzed by tetramer staining and enzyme‐linked immunospot assay. Histological analysis revealed dense infiltration of CD8 + T cells in some lesions in patients who had received the SVN‐2B peptide vaccine. A high rate of programmed cell death ligand 1 expression in cancer cells was observed in these cases, indicating that CTLs were induced by SVN‐2B peptide vaccination and had infiltrated the lesions. The lack of a significant antitumor effect was most likely attributable to the expression of immune checkpoint molecules. These findings suggest that the combination of a tumor‐specific peptide vaccine and an ICI might be a promising approach to the treatment of pancreatic carcinoma in the future. Abstract : Autopsy analysis using pancreatic cancer cases with survivin 2B peptide vaccination revealed that numbers of CTLs were trapped in cancer stroma. This result indicates that inhibition of cancer stroma might be the next target for effective cancer immunotherapy.